Biodegradable polyester composition, preparation method thereof and biodegradable non-woven fabric

By using aliphatic-aromatic copolyester and aliphatic polyester composition with differentiated molecular weights, the problem of insufficient flexibility and elasticity of existing non-woven fabrics is solved, and the preparation of non-woven fabrics with high performance and low energy consumption is achieved.

CN119875315APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311378106.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing biodegradable nonwovens have shortcomings in terms of flexibility and elasticity, and the high processing temperature leads to an increase in energy consumption, and fails to effectively utilize degradable polyesters of different molecular weights and compositions.

Method used

A biodegradable polyester composition consisting of aliphatic-aromatic copolyester and aliphatic polyester with differentiated molecular weights, prepared by blending, extrusion, cooling and pelletizing processes to form a nonwoven fabric with excellent properties.

Benefits of technology

The obtained non-woven fabric has excellent rigid and tough balance characteristics, high tensile strength, high elongation at break, good feel, simple processing process and stable structure, which overcomes the problem of slow crystallization of traditional polyester.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875315A_ABST
    Figure CN119875315A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and discloses a biodegradable polyester composition and a preparation method thereof, and a biodegradable non-woven fabric, the composition contains aliphatic-aromatic copolyester and aliphatic polyester, the aliphatic-aromatic copolyester is a copolymer containing repetitive units represented by formulas (I) and (II); in the # imgabs0 # formula (I), m1 is equal to 4, and n1 is equal to 2, 3, 4, 5, 6, 7 or 8; in the aliphatic-aromatic copolyester, the content of the repetitive unit as shown in the formula (II) is 40-50 mol%; the weight-average molecular weight of the aliphatic-aromatic copolyester is 45000 g / mol to 75000 g / mol; the aliphatic polyester is poly (butylene succinate), and the weight-average molecular weight of the aliphatic polyester is 100000 g / mol to 130000 g / mol. The obtained non-woven fabric has good comprehensive mechanical performance and hand feeling and excellent rigid-tough balance characteristic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer materials, and in particular, relates to a biodegradable polyester composition, a method for preparing the biodegradable polyester composition, and a biodegradable nonwoven fabric prepared from the biodegradable polyester composition. Background Art

[0002] Nonwoven fabrics, also known as non-woven fabrics, are a type of fabric that does not require spinning and weaving. The fibers are oriented or randomly arranged to form a fiber mesh structure, and then reinforced by mechanical, thermal bonding or chemical methods. Nonwoven fabrics are widely used in medical, sanitary, clothing, filtration, insulation, food packaging and agriculture. At present, with the continuous improvement of environmental protection standards, it has become a trend to use more environmentally friendly biodegradable plastics to replace traditional non-degradable plastics. Therefore, biodegradable nonwoven fabrics are a new type of product that has both practicality and sustainable development characteristics.

[0003] The main non-woven fabric processing methods currently available on the market are meltblowing and spunbond. Compared with meltblown fabrics, spunbond non-woven fabrics have greater breaking strength and elongation, can meet various performance requirements, and have reliable strength. The raw materials used to make biodegradable spunbond non-woven fabrics are mostly polylactic acid (PLA) and polybutylene succinate (PBS). Non-woven fabrics prepared from a single component often have some disadvantages in performance, such as non-woven fabrics prepared from a single PLA have low bonding flexibility, high roughness, hard touch, and poor texture and softness. In order to improve the shortcomings, methods such as mixing, copolymerization or blending of different materials can be used.

[0004] Patent document CN115028820A discloses a melt-spinnable PBS and its preparation method and application in the preparation of non-woven fabrics, improves the molecular structure of PBS or introduces terephthalic acid or furandicarboxylic acid, and prepares non-woven fabrics by a spunbond method. Patent document CN102395720A provides a biodegradable spunbond non-woven fabric, which is mixed with two degradable materials, one of which is PLA or PLA copolymer, and the other is PBS or PBS copolymer. Patent document CN101331257 discloses a spunbond non-woven fabric mixed with PBS and PLA. The above-mentioned prior art uses PLA and PBS, both of which are materials with high glass transition temperature, crystallinity or modulus, so the prepared non-woven fabric has the problems of poor softness and low elasticity, and the required processing temperature is also high, thereby increasing energy consumption.

[0005] In addition, degradable aliphatic-aromatic copolyesters have good elasticity and softness, such as polybutylene succinate / terephthalate copolymer (PBST) and polybutylene adipate / terephthalate copolymer (PBAT). However, due to the low crystallization temperature and slow crystallization rate of this type of polyester, it cannot meet the processing conditions of spunbond nonwovens and is only used in the meltblown field.

[0006] Moreover, none of the above prior arts involve the problem of the combination and use of degradable polyesters with different molecular weights and different compositions. This problem is of special significance to the field of degradable polyesters, because the molecular weight of degradable polyesters will decrease during storage, which will lead to their inability to meet the original demand. If they are properly utilized, it will reduce resource waste and have significant economic and social benefits. Summary of the invention

[0007] In order to improve the shortcomings of the prior art and further improve the utilization rate of biodegradable polyesters, the present invention provides a biodegradable polyester composition, a preparation method thereof and a biodegradable non-woven fabric. The two polyesters in the composition have differentiated molecular weights, which can realize the scientific utilization of materials with different molecular weights. The obtained non-woven fabric has excellent performance and excellent rigidity-toughness balance characteristics, and is suitable for disposable sanitary products, sheets, filtration and various packaging bags, etc.

[0008] The first aspect of the present invention provides a biodegradable polyester composition, which contains an aliphatic-aromatic copolyester and an aliphatic polyester, wherein the content of the aliphatic-aromatic copolyester is 3-20 wt % and the content of the aliphatic polyester is 80-97 wt % based on the total weight of the aliphatic-aromatic copolyester and the aliphatic polyester;

[0009] The aliphatic-aromatic copolyester is a copolymer containing repeating units represented by formula (I) and (II);

[0010]

[0011] In formula (I), m 1 =4,n 1 =2, 3, 4, 5, 6, 7 or 8;

[0012] In the aliphatic-aromatic copolyester, based on the total molar number of the repeating units represented by formula (I) and (II), the content of the repeating unit represented by formula (II) is 40-50 mol%; the weight average molecular weight of the aliphatic-aromatic copolyester is 45000 g / mol-75000 g / mol;

[0013] The aliphatic polyester is polybutylene succinate, and the weight average molecular weight of the aliphatic polyester is 100000 g / mol-130000 g / mol.

[0014] The second aspect of the present invention provides a method for preparing the above-mentioned biodegradable polyester composition, which comprises: blending the components of the composition to obtain a mixed material; extruding, cooling and pelletizing the mixed material to obtain the biodegradable polyester composition.

[0015] The third aspect of the present invention provides a biodegradable non-woven fabric, which is prepared by using the above-mentioned biodegradable polyester composition.

[0016] The non-woven fabric prepared by using the composition of the present invention has good comprehensive mechanical properties and good hand feel. While ensuring high tensile strength, it also achieves high elongation at break, has excellent rigidity-toughness balance characteristics, has a simple preparation method, has a stable structure during processing, has uniform thickness of the non-woven fabric, and has fast and stable production.

[0017] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is the crystallization peak of composition A1 in Example 1.

[0019] Figure 2 It is the crystallization peak of the polybutylene succinate / terephthalate copolymer in Comparative Example 6. DETAILED DESCRIPTION

[0020] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0021] According to a first aspect of the present invention, the present invention provides a biodegradable polyester composition, the composition comprising an aliphatic-aromatic copolyester and an aliphatic polyester, wherein the content of the aliphatic-aromatic copolyester is 3-20 wt % and the content of the aliphatic polyester is 80-97 wt % based on the total weight of the aliphatic-aromatic copolyester and the aliphatic polyester;

[0022] The aliphatic-aromatic copolyester is a copolymer containing repeating units represented by formula (I) and (II);

[0023]

[0024] In formula (I), m 1 =4,n 1 =2, 3, 4, 5, 6, 7 or 8;

[0025] In the aliphatic-aromatic copolyester, based on the total molar number of the repeating units represented by formula (I) and (II), the content of the repeating unit represented by formula (II) is 40-50 mol%; the weight average molecular weight of the aliphatic-aromatic copolyester is 45000 g / mol-75000 g / mol;

[0026] The aliphatic polyester is polybutylene succinate, i.e., contains repeating units represented by formula (III);

[0027]

[0028] In formula (III), m 2 =4,n 2 =2;

[0029] The weight average molecular weight of the aliphatic polyester is 100000 g / mol-130000 g / mol.

[0030] In the composition of the present invention, the high crystallization rate of the aliphatic polyester ensures the smooth and high-speed processing of the non-woven fabric, and the high crystallinity provides mechanical strength for the non-woven fabric; the aliphatic-aromatic copolyester provides the non-woven fabric with a comfortable feel and elasticity, and the touch and mechanical properties of the non-woven fabric can be adjusted by the ratio of the two, which is easy to implement and low in cost.

[0031] Preferably, based on the total weight of the aliphatic-aromatic copolyester and the aliphatic polyester, the content of the aliphatic-aromatic copolyester is 5-15 wt %, and the content of the aliphatic polyester is 85-95 wt %.

[0032] Preferably, in the aliphatic-aromatic copolyester, based on the total molar number of the repeating units represented by formula (I) and (II), the content of the repeating unit represented by formula (II) is 42-47 mol%.

[0033] According to the present invention, the weight average molecular weight of the composition may be 94400-119000 g / mol.

[0034] In the present invention, after the composition is isothermally heated at 200° C. for 5 minutes to eliminate the thermal history, the half-peak width of the crystallization peak is less than 10° C. under the condition of cooling at 10° C. / min.

[0035] According to the present invention, according to the performance requirements, the composition further contains an auxiliary agent, which includes but is not limited to an antioxidant, a chain extender, talcum powder, etc., and the amount added is the conventional amount in the art. The auxiliary agent can be various types conventionally used in the prior art. For example, the antioxidant can be a hindered phenol antioxidant, a phosphite antioxidant, a pentaerythritol ester antioxidant, etc.

[0036] In the present invention, the aliphatic-aromatic copolyester and the aliphatic polyester are random copolymers, and their sources are not particularly limited. They can be prepared by conventional means in the art or commercially available, as long as the above-mentioned parameter requirements are met. The polyester used in the embodiments of the present invention is prepared.

[0037] The aliphatic-aromatic copolyester and aliphatic polyester in the present invention can be prepared by the following method, which specifically comprises the following steps:

[0038] (1) contacting a diacid, an ester thereof, an anhydride thereof or a mixture thereof, a diol, and a first catalyst in a reaction vessel under vacuum conditions and prepolymerizing the contacted diacid to obtain a prepolymer; the diacid is an organic dicarboxylic acid, such as terephthalic acid, a dibasic fatty acid having 4 to 10 carbon atoms (such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid); and the diol is butanediol;

[0039] (2) contacting the prepolymer with a second catalyst to carry out a vacuum polycondensation reaction to obtain a polyester.

[0040] The present invention has no particular limitation on the mixing order of the components in the reaction system, and the amount of each component used is based on the content of the structural units required by the product.

[0041] According to the present invention, the reaction conditions of each step may also adopt conventional conditions in the art.

[0042] Specifically, in step (1), the reaction conditions of the prepolymerization may include: reaction temperature of 190-250° C.; vacuum degree of 200-600 Pa; reaction time of 1-3 hours, or until the small molecules in the reaction system are almost exhausted and the fraction temperature remains unchanged.

[0043] In step (2), the reaction conditions of the vacuum polycondensation reaction may include: reaction temperature of 200-300° C.; vacuum degree of <300 Pa; and reaction time of 3-12 hours.

[0044] The present invention does not particularly limit the catalyst used in the polymerization reaction and its amount, and can be various conventional catalysts and conventional catalyst amounts for synthesizing polyester. The catalysts used in step (1) and step (2) can be the same or different. For example, the catalyst used in step (1) can be selected from at least one of compounds of metal titanium, antimony and tin; the catalyst used in step (2) can be selected from compounds of rare earth metal Ln and mixtures thereof, wherein the rare earth metal Ln is selected from at least one of lanthanide elements, scandium and yttrium.

[0045] According to the present invention, step (1) and step (2) can be carried out in the same reactor or in different reactors, that is, the prepolymer can be taken out and transferred to another reactor to continue the subsequent polymerization reaction.

[0046] According to the present invention, nitrogen is usually used as protection in the reaction system, but other atmospheres, including air, may also be used.

[0047] According to the second aspect of the present invention, the present invention provides a method for preparing the above-mentioned biodegradable polyester composition, which comprises: blending the components of the composition to obtain a mixture; extruding, cooling and pelletizing the mixture to obtain the biodegradable polyester composition.

[0048] In the present invention, operations such as blending and extrusion can be performed using common equipment and conventional parameters in the art. For example, the components can be added to a high-speed mixer for mixing; the mixed material can be added to a twin-screw extruder for extrusion.

[0049] The third aspect of the present invention provides a biodegradable non-woven fabric, which is prepared by using the above-mentioned biodegradable polyester composition.

[0050] According to the present invention, the nonwoven fabric is prepared by a spunbond method, and the device used can be a spunbond nonwoven fabric preparation device known in the art, and the preparation is performed using conventional process parameters. For example, the conditions of the spunbond method include: an extrusion temperature of 190-270°C, a web forming speed of 15-20m / min, and a hot rolling temperature of 100-110°C.

[0051] The substances and parameters not limited in the present invention can be selected according to the existing technology and belong to the conventional technical means in this field.

[0052] The present invention will be further described below with reference to the following examples, but is not limited to these examples.

[0053] In the following examples and comparative examples, the relevant raw materials and data were obtained by the following method:

[0054] Polybutylene succinate / terephthalate copolymer, the molar fraction of repeating unit (II) is 47%, the weight average molecular weight (M w) is 45000g / mol, and the preparation method thereof comprises: adding 0.47mol terephthalic acid, 0.53mol succinic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 6.5 hours to obtain a polybutylene succinate / terephthalate product.

[0055] The polybutylene succinate / terephthalate copolymer has a molar fraction of 44% of the repeating unit (II) and a weight average molecular weight (Mw) of 68000 g / mol. The preparation method thereof comprises: adding 0.44 mol of terephthalic acid, 0.56 mol of succinic acid and 1.2 mol of 1,4-butanediol and 1 mmol of a catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Adding 0.1 mmol of a catalyst Cat2 (lanthanum acetylacetonate), stirring and heating continuously, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 8 hours to obtain a polybutylene succinate / terephthalate product.

[0056] The polybutylene succinate / terephthalate copolymer has a molar fraction of 42% of the repeating unit (II) and a weight average molecular weight (Mw) of 75000 g / mol. The preparation method comprises: adding 0.42 mol of terephthalic acid, 0.58 mol of succinic acid and 1.2 mol of 1,4-butanediol and 1 mmol of a catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Adding 0.1 mmol of a catalyst Cat2 (lanthanum acetylacetonate), continuing stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 8.5 hours to obtain a polybutylene succinate / terephthalate product.

[0057] The polybutylene succinate / terephthalate copolymer has a molar fraction of 46% of the repeating unit (II) and a weight average molecular weight (Mw) of 65000 g / mol. The preparation method thereof comprises: adding 0.46 mol of terephthalic acid, 0.54 mol of succinic acid and 1.2 mol of 1,4-butanediol and 1 mmol of a catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Adding 0.1 mmol of a catalyst Cat2 (lanthanum acetylacetonate), stirring and heating continuously, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 8 hours to obtain a polybutylene succinate / terephthalate product.

[0058] Polybutylene succinate / terephthalate copolymer, the molar fraction of repeating unit (II) is 40%, the weight average molecular weight (M w ) is 45000g / mol, and the preparation method thereof comprises: adding 0.4mol terephthalic acid, 0.6mol succinic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Adding 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continuing stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 6.5 hours to obtain a polybutylene succinate / terephthalate product.

[0059] Polybutylene succinate / terephthalate copolymer, the molar fraction of repeating unit (II) is 49%, the weight average molecular weight (M w ) is 45000g / mol, and the preparation method thereof comprises: adding 0.49mol terephthalic acid, 0.51mol succinic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 6.5 hours to obtain a polybutylene succinate / terephthalate product.

[0060] Polybutylene succinate / terephthalate copolymer, the molar fraction of repeating unit (II) is 47%, the weight average molecular weight (M w) is 30000g / mol, and the preparation method thereof comprises: adding 0.47mol terephthalic acid, 0.53mol succinic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 4.5 hours to obtain a polybutylene succinate / terephthalate product.

[0061] Polybutylene succinate / terephthalate copolymer, the molar fraction of repeating unit (II) is 47%, the weight average molecular weight (M w ) is 75000g / mol, and the preparation method thereof comprises: adding 0.47mol terephthalic acid, 0.53mol succinic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 8.5 hours to obtain a polybutylene succinate / terephthalate product.

[0062] Poly (butylene adipate / terephthalate copolymer), the molar fraction of repeating unit (II) is 47%, the weight average molecular weight (M w ) is 55000g / mol, and the preparation method thereof comprises: adding 0.47mol terephthalic acid, 0.53mol adipic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 6.5 hours to obtain a poly(adipate / butylene terephthalate) product.

[0063] Poly(pimelic acid / butylene terephthalate) copolymer, the molar fraction of repeating unit (II) is 47%, the weight average molecular weight (M w) is 45000g / mol, and the preparation method thereof comprises: adding 0.47mol terephthalic acid, 0.53mol pimelic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 5.5 hours to obtain a polypimelic acid / butylene terephthalate product.

[0064] Poly (azelaic acid / butylene terephthalate copolymer), the molar fraction of repeating unit (II) is 47%, the weight average molecular weight (M w ) is 45000g / mol, and the preparation method thereof comprises: adding 0.47mol terephthalic acid, 0.53mol azelaic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 5.5 hours to obtain a polyazelaic acid / butylene terephthalate product.

[0065] The poly (sebacic acid / butylene terephthalate) copolymer has a molar fraction of 50% of the repeating unit (II) and a weight average molecular weight (Mw) of 49000 g / mol. The preparation method thereof comprises: adding 0.5 mol of terephthalic acid, 0.5 mol of sebacic acid and 1.2 mol of 1,4-butanediol, and 1 mmol of a catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2.5 hours). Adding 0.1 mmol of a catalyst Cat2 (lanthanum acetylacetonate), continuing stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 5.5 hours to obtain a poly (sebacic acid / butylene terephthalate) product.

[0066] Polybutylene succinate / butylene glycol, weight average molecular weight (M w) is 130000g / mol, and the preparation method thereof comprises: adding 1mol succinic acid and 1.2mol 1,4-butanediol, and 0.5mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Adding 0.05mmol catalyst Cat2 (lanthanum acetylacetonate), continuing stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 9 hours to obtain a polysuccinic acid / butylene glycol product.

[0067] Polybutylene succinate / butylene glycol, with a weight average molecular weight (Mw) of 100000 g / mol, is prepared by adding 1 mol of succinic acid and 1.2 mol of 1,4-butanediol, and 0.5 mmol of catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.05 mmol of catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 7.5 hours to obtain a polybutylene succinate / butylene glycol product.

[0068] Polybutylene succinate, with a weight average molecular weight (Mw) of 120,000 g / mol, is prepared by adding 1 mol of succinic acid and 1.2 mol of 1,4-butanediol, and 0.5 mmol of a catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.05 mmol of a catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 8 hours to obtain a polybutylene succinate product.

[0069] Polybutylene succinate / butylene glycol, with a weight average molecular weight (Mw) of 125000 g / mol, is prepared by adding 1 mol of succinic acid and 1.2 mol of 1,4-butanediol, and 0.5 mmol of catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.05 mmol of catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 8.5 hours to obtain a polybutylene succinate / butylene glycol product.

[0070] Polybutylene succinate / butylene glycol, weight average molecular weight (M w ) is 90000g / mol, and the preparation method thereof comprises: adding 1mol succinic acid and 1.2mol 1,4-butanediol, and 0.5mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Adding 0.05mmol catalyst Cat2 (lanthanum acetylacetonate), continuing stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 7 hours to obtain a polysuccinic acid / butylene glycol product.

[0071] Polybutylene succinate / butylene glycol, weight average molecular weight (M w ) is 150000 g / mol, and the preparation method thereof comprises: adding 1 mol of succinic acid and 1.2 mol of 1,4-butanediol, and 0.5 mmol of catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Adding 0.05 mmol of catalyst Cat2 (lanthanum acetylacetonate), continuing stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 12 hours to obtain a polysuccinic acid / butylene glycol product.

[0072] 1. The weight average molecular weight of copolyester and polyester was determined by gel permeation chromatography (GPC). GPC used tetrahydrofuran as mobile phase and polystyrene standard samples for calibration.

[0073] 2. The composition of the copolyester was determined by nuclear magnetic resonance (NMR) method. The NMR experiment was performed on an Agilent 600 MHz nuclear magnetic resonance instrument, the solvent was CDCl3, and the test temperature was room temperature.

[0074] 3. The tensile test was performed using an INSTRON-5965 tensile tester, INSTRON, USA.

[0075] 4. The crystallization experiment used a TA-Q-100 differential scanning calorimeter, TA Company, USA. The sample was first isothermally heated at 200 °C for 5 minutes to eliminate the thermal history, and then cooled at 10 °C / min to record the crystallization exothermic curve.

[0076] Example 1

[0077] Biodegradable polyester composition: poly(butylene terephthalate / succinic acid) copolymer, NMR determination of the molar fraction of repeating unit (II) is 47%, the weight average molecular weight (M w ) is 45000g / mol; poly(butylene succinate / butylene glycol), weight average molecular weight (M w ) is 130000 g / mol; hindered phenol antioxidant 300; based on the total weight of poly(butylene succinate / terephthalate) copolymer and poly(butylene succinate / terephthalate), the content of poly(butylene succinate / terephthalate) copolymer is 10 weight%, and the content of poly(butylene succinate / terephthalate) is 90 weight%; the content of hindered phenol antioxidant 300 is 2‰ of the total weight of poly(butylene succinate / terephthalate) copolymer and poly(butylene succinate / terephthalate).

[0078] The above components were pre-mixed with a high-speed mixer, and then extruded, cooled, and pelletized by a twin-screw extruder to obtain composition A1. The crystal peak of composition A1 is as follows Figure 1 shown.

[0079] The above polymer A1 was dried at 60°C for 5 hours and then added to a spunbond nonwoven fabric processing equipment. The screw temperature of the spunbond equipment was set at 190-220°C, the web speed was 17m / min, and the hot rolling temperature was 105°C to obtain a nonwoven fabric B1. The performance parameters of the composition A1 and the nonwoven fabric B1 are shown in Table 1.

[0080] Example 2

[0081] The same as Example 1, except that: the molar fraction of repeating unit (II) in the polysuccinic acid / butylene terephthalate copolymer is 44%, and the weight average molecular weight (Mw) is 68000g / mol; the weight average molecular weight (Mw) of polysuccinic acid / butylene glycol is 100000g / mol. Based on the total weight of polysuccinic acid / butylene terephthalate copolymer and polysuccinic acid / butylene glycol, the content of polysuccinic acid / butylene terephthalate copolymer is 15% by weight, and the content of polysuccinic acid / butylene glycol is 85% by weight. Composition A2 and nonwoven fabric B2 are obtained, and the performance parameters are shown in Table 1.

[0082] Example 3

[0083] Same as Example 1, except that: the molar fraction of repeating unit (II) in the polysuccinic acid / butylene terephthalate copolymer is 42%, and the weight average molecular weight (Mw) is 75000 g / mol; the weight average molecular weight (Mw) of polysuccinic acid / butylene glycol is 100000 g / mol. Based on the total weight of polysuccinic acid / butylene terephthalate copolymer and polysuccinic acid / butylene glycol, the content of polysuccinic acid / butylene terephthalate copolymer is 5 weight%, and the content of polysuccinic acid / butylene glycol is 95 weight%. Composition A3 and nonwoven fabric B3 are obtained, and the performance parameters are shown in Table 1.

[0084] Example 4

[0085] The same as Example 1, except that: the molar fraction of repeating unit (II) in the polysuccinic acid / butylene terephthalate copolymer is 46%, and the weight average molecular weight (Mw) is 65000 g / mol; the weight average molecular weight (Mw) of polysuccinic acid / butylene glycol is 120000 g / mol. Based on the total weight of polysuccinic acid / butylene terephthalate copolymer and polysuccinic acid / butylene glycol, the content of polysuccinic acid / butylene terephthalate copolymer is 3 weight%, and the content of polysuccinic acid / butylene glycol is 97 weight%. Composition A4 and nonwoven fabric B4 are obtained, and the performance parameters are shown in Table 1.

[0086] Example 5

[0087] Same as Example 1, except that: the molar fraction of repeating unit (II) in the polysuccinic acid / butylene terephthalate copolymer is 46%, and the weight average molecular weight (Mw) is 65000 g / mol; the weight average molecular weight (Mw) of polysuccinic acid / butylene glycol is 125000 g / mol. Based on the total weight of polysuccinic acid / butylene terephthalate copolymer and polysuccinic acid / butylene glycol, the content of polysuccinic acid / butylene terephthalate copolymer is 20% by weight, and the content of polysuccinic acid / butylene glycol is 80% by weight. Composition A5 and nonwoven fabric B5 are obtained, and the performance parameters are shown in Table 1.

[0088] Example 6

[0089] Same as Example 1, except that the molar fraction of the repeating unit (II) in the polybutylene succinate / terephthalate copolymer is 40%. Composition A6 and nonwoven fabric B6 were obtained, and their performance parameters are shown in Table 1.

[0090] Example 7

[0091] Same as Example 1, except that the molar fraction of the repeating unit (II) in the polybutylene succinate / terephthalate copolymer is 49%. Composition A7 and nonwoven fabric B7 were obtained, and their performance parameters are shown in Table 1.

[0092] Example 8

[0093] Same as Example 1, except that the poly(succinic acid / butylene terephthalate) copolymer is replaced with a poly(adipate / butylene terephthalate) copolymer, and the weight average molecular weight (M w ) is 55000 g / mol. Composition A8 and nonwoven fabric B8 were obtained, and the performance parameters are shown in Table 1.

[0094] Example 9

[0095] Same as Example 1, except that the poly(succinic acid / butylene terephthalate) copolymer is replaced with a poly(pimelic acid / butylene terephthalate) copolymer, and the weight average molecular weight (M w ) is 45000 g / mol. Composition A9 and nonwoven fabric B9 were obtained, and the performance parameters are shown in Table 1.

[0096] Example 10

[0097] Same as Example 1, except that the poly(succinic acid / butylene terephthalate) copolymer is replaced with a poly(azelaic acid / butylene terephthalate) copolymer, and the weight average molecular weight (M w ) is 45000 g / mol. Composition A10 and nonwoven fabric B10 were obtained, and the performance parameters are shown in Table 1.

[0098] Embodiment 11

[0099] Same as Example 1, except that the poly(succinic acid / butylene terephthalate) copolymer was replaced with a poly(sebacic acid / butylene terephthalate) copolymer, and the molar fraction of the repeating unit (II) was 50% by NMR, and the weight average molecular weight (Mw) was 49000 g / mol. Composition A11 and nonwoven fabric B11 were obtained, and the performance parameters were shown in Table 1.

[0100] Comparative Example 1

[0101] The same as Example 1, except that: based on the total weight of the polybutylene succinate / terephthalate copolymer and the polybutylene succinate / terephthalate, the content of the polybutylene succinate / terephthalate copolymer is 2 weight percent, and the content of the polybutylene succinate / terephthalate is 98 weight percent. Composition CA1 and nonwoven fabric CB1 were obtained, and the performance parameters were shown in Table 1.

[0102] Comparative Example 2

[0103] The same as Example 1, except that: based on the total weight of the polybutylene succinate / terephthalate copolymer and the polybutylene succinate / terephthalate, the content of the polybutylene succinate / terephthalate copolymer is 30% by weight, and the content of the polybutylene succinate / terephthalate is 70% by weight. Composition CA2 and nonwoven fabric CB2 were obtained, and the performance parameters were shown in Table 1.

[0104] Comparative Example 3

[0105] Same as Example 1, except that the weight average molecular weight (M w ) is 30000 g / mol. Composition CA3 and nonwoven fabric CB3 were obtained, and the performance parameters are shown in Table 1.

[0106] Comparative Example 4

[0107] Same as Example 1, except that the weight average molecular weight (M w ) is 90000 g / mol. Composition CA4 and nonwoven fabric CB4 were obtained, and the performance parameters are shown in Table 1.

[0108] Comparative Example 5

[0109] Same as Example 1, except that the weight average molecular weight (M w ) is 150000 g / mol. Composition CA5 and nonwoven fabric CB5 were obtained, and the performance parameters are shown in Table 1.

[0110] Comparative Example 6

[0111] Same as Example 1, except that only poly(butylene succinate / terephthalate) copolymer was used, wherein the molar fraction of repeating unit (II) was 47%, and the weight average molecular weight (M w ) is 75000 g / mol. Trial production of nonwoven fabrics. The crystallization peak of poly(butylene succinate / terephthalate) copolymer is as follows Figure 2 The performance parameters are shown in Table 1.

[0112] Comparative Example 7

[0113] Same as Example 1, except that only poly(succinic acid / butylene glycol) was used, and its weight average molecular weight (M w ) is 100000 g / mol. Nonwoven fabric CB7 was obtained, and the performance parameters are shown in Table 1.

[0114] Table 1

[0115]

[0116] From Table 1 and Figure 1-2It can be seen that the biodegradable non-woven fabric of the present invention has good comprehensive mechanical properties and hand feel. While ensuring high tensile strength, it also achieves high elongation at break, and has excellent rigidity-toughness balance characteristics; and it has good processability and formability, overcoming the common disadvantage of slow crystallization of polyester, fast forming, and stable shape. The preparation method of the composition of the present invention is simple and easy, and the material composition can be adjusted by mechanical blending to obtain excellent and adjustable mechanical properties. The combination of polyesters with different molecular chain structures and different molecular weights, on the one hand, ensures processability, and on the other hand, makes the prepared non-woven fabric have excellent comprehensive performance.

[0117] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A biodegradable polyester composition, characterized in that: The composition contains aliphatic-aromatic copolyester and aliphatic polyester, wherein the content of aliphatic-aromatic copolyester is 3-20 weight percent and the content of aliphatic polyester is 80-97 weight percent based on the total weight of the aliphatic-aromatic copolyester and the aliphatic polyester; The aliphatic-aromatic copolyester is a copolymer containing repeating units represented by formula (I) and (II); In formula (I), m1=4, n1=2, 3, 4, 5, 6, 7 or 8; In the aliphatic-aromatic copolyester, based on the total molar number of the repeating units represented by formula (I) and (II), the content of the repeating unit represented by formula (II) is 40-50 mol%; the weight average molecular weight of the aliphatic-aromatic copolyester is 45000 g / mol-75000 g / mol; The aliphatic polyester is polybutylene succinate, and the weight average molecular weight of the aliphatic polyester is 100000 g / mol-130000 g / mol.

2. The biodegradable polyester composition according to claim 1, wherein Based on the total weight of the aliphatic-aromatic copolyester and the aliphatic polyester, the content of the aliphatic-aromatic copolyester is 5-15 wt %, and the content of the aliphatic polyester is 85-95 wt %.

3. The biodegradable polyester composition according to claim 1, wherein In the aliphatic-aromatic copolyester, based on the total molar number of the repeating units represented by formula (I) and (II), the content of the repeating unit represented by formula (II) is 42-47 mol%.

4. The biodegradable polyester composition according to claim 1, wherein The weight average molecular weight of the composition is 94400-119000 g / mol.

5. The biodegradable polyester composition according to claim 1, wherein After the composition is isothermally heated at 200° C. for 5 minutes to eliminate the thermal history, the half-peak width of the crystallization peak is less than 10° C. under the condition of cooling at 10° C. / min.

6. The biodegradable polyester composition according to claim 1, wherein The composition further contains an auxiliary agent, which is selected from at least one of an antioxidant, a chain extender and talc.

7. The method for preparing the biodegradable polyester composition according to any one of claims 1 to 6, characterized in that: The preparation method comprises: blending the components of the composition to obtain a mixed material; and extruding, cooling and pelletizing the mixed material to obtain the biodegradable polyester composition.

8. A biodegradable nonwoven fabric, characterized in that: The nonwoven fabric is prepared by using the biodegradable polyester composition described in any one of claims 1 to 6.

9. The biodegradable nonwoven fabric according to claim 8, wherein: The nonwoven fabric is produced by a spunbond method.

10. The biodegradable nonwoven fabric according to claim 9, wherein: The conditions of the spunbond method include: an extrusion temperature of 190-270°C, a web forming speed of 15-20 m / min, and a hot rolling temperature of 100-110°C.

Citation Information

Patent Citations

  • Biodegradable nonwoven fabric and fiber product using the same

    CN102395720A

  • Melt-spinnable poly (butylene succinate) as well as preparation method and application thereof

    CN115028820A